An introduction of colonial framework from watanic jurisprudence analysis: A case study on the malay states - Wan Ahmad Fauzi, Wan Husain (NUN Gemilang ENT., 2024)
Colonisation and decolonisation are popular research subjects, but they lack legal definitions. Colonisation brings the subject of colonialism that invites broader aspects of research. Most of the discussions about the impact of colonialism upon nation-states do not distinguish between sovereign and colonised states. This attitude is contagious from the habit of stereotyping that everything that came under British influence was colonised and under colonial rule. This is a qualitative study of legal history employing watanic jurisprudence analysis. The Malay states become a case study because the legal historical texts prove otherwise than what the public perceives. Hence, this article aims to construct the colonial framework from the perspective of international law. This study is essential because many writings employ the words ‘colony’, ‘colonisation’, ‘under colonial rule’, and ‘colonised states’ arbitrarily without first examining the legal position of any state, including the Malay states that were once under the influence of the British. The above attitude renders the study of many aspects of ‘the so-called colonised Malay states’ biased and constructed from the wrong foundation. In conclusion, there must be evidence of the transfer of internal sovereignty to a foreign authority to constitute a colonisation. From this premise, the Malay states were not colonised, and the sovereignty of the Malay rulers continues to this day as enshrined in Article 181(1) of the Federal Constitution.